BLS Training and Welders’ Knowledge and Attitudes Toward Workplace Emergency Management: A Study in the Erection Area at PT X, Karimun Regency - Amaliah, Rizqi Ulla; Parisma, Wan Intan; Wiranto, Wiranto (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Welding work in the construction sector carries a high risk of workplace accidents that may require emergency response, including sudden cardiac arrest. Basic life support is a vital skill to sustain victims until medical assistance arrives. Objective: This study analyzed the relationship between basic life support training and welders’ knowledge and attitudes toward managing workplace accidents in the erection area of PT X, Karimun Regency. Method: This quantitative study used a cross-sectional design and involved 32 welders recruited through total sampling. Data were collected using a questionnaire that had been tested for validity and reliability, then analyzed using univariate and bivariate analyses with the Chi-square test at a significance level of 0.05. Result and Discussion: A significant association was found between basic life support training and workers’ knowledge (p < 0.001); 94.4% of trained workers demonstrated a high level of knowledge. However, no significant association was identified between training and workers’ attitudes (p = 0.145), although a tendency toward more positive attitudes was observed among trained workers. Conclusions: Basic life support training plays an important role in improving welders’ knowledge, whereas developing positive attitudes may require additional strategies such as simulation-based practice, habituation, and reinforcement of a safety culture